LOWER KUTAI BASIN CONFIGURATION FROM MAGNETOTELLURIC, SEISMIC, AND GRAVITY DATA - Misnia Irawati, Selvi
Kutai Basin is the deepest and widest basin in Indonesia. The research area is located at Lower Kutai Basin (LKB) and the main structure of this area is anticlinorium Samarinda which has NE – SW direction. This area is well-known as one of the productive basins for hydrocarbon in East Kalimantan, which has black shale as a source rock. This research aims at describing the LKB configuration due to magnetotelluric (MT), seismic, and gravity data. Before modeling, we need to analyze the MT data using phase tensor. This analysis shows that most of the data denote as ellipses and have low beta value (i.e. -3? < ? < 3?). It indicates that MT data have 2D character. Furthermore, the calculations of phase tensor elipticity show that the direction of geoelectrical strike is N 30?E. This result is in agreement with the geological strike that has NE – SW direction. We make 2D modeling using WinGLink to obtain the resistivity configuration of LKB. The MT models are integrated with the seismic and gravity models. In this study, MT and gravity models are in depth domain while the seismic is in the time domain. We need to convert time to depth of seismic using velocity data. The integration of MT, seismic, gravity models shows that LKB configuration is composed of sandstone, black shale, claystone, and a basement. The conductive zone of MT models has a medium density and interpreted as black shale at >2 km depth. The conductivity of black shale is generated by thermal alteration that changes the internal minerals of the rock. Hence, it reduces the resistivity value. Besides that, the integrated models show that there is significant vertical offset subsurface, i.e. faults.